PENGARUH KOMITE AUDIT, LAMA PERIKATAN AUDIT DAN AUDIT CAPACITY STRESS TERHADAP KUALITAS AUDIT - Arum Ardianingsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Financial scandals occurred not only in America but also in Indonesia . The impact of the scandal was carried  out  order  conditions  and  regulatory  reform  business  practices  .  Sarbanes  Oxley  Act  (  SOX  ) make  improvements  and  tightening  the  audit  and  its  supporting  components.  Efforts  to  improve  the quality of the audits performed by requiring a minimum level per year, limiting the engagement period ( tenure ) auditors and their clients , as well as establish an audit committee ( Baridwan and Hariani , 2010  ).  This  study  aims  to  provide  empirical  evidence  of  the  influence  of  the  audit  committee  ,  the audit  engagement  and  long  stress  audit  capacity  to  audit  quality.  The  research  method  used  logistic regression  with sampling techniques using purposive sampling. Data  using banking companies listed on the Stock Exchange 2008-2012 period . The results showed that the audit committee ( X1 ) had no significant  effect  on  audit  quality  (  Y  )  with  a  significance  level  that  is  equal  to  0,999,  the  audit engagement length ( X2 ) had no significant effect on audit quality ( Y ) with a significance level that is equal to 0.913 , Audit stress capacity ( X3 ) had no significant effect on audit quality ( Y ) with a significance level that is equal to 0.913.  Keywords :  quality of the audit, the audit committee, the audit and the audit engagement old stress capacity.